A gendered media analysis of the prime ministerial ascension of Gillard and Turnbull: he's 'taken back the reins' and she's 'a backstabbing' murderer. Issue 4 (2nd October 2017) - Williams, Blair
ABSTRACT: In contemporary Australian politics, challenges to the Prime Ministerial role have become more common. Australia saw five Prime Ministers from 2010 to 2015 including Australia's first ever woman Prime Minister, Julia Gillard. A stark contrast is evident in media portrayals of Gillard and her male counterparts, apparent most recently in the response to Malcolm Turnbull's ascension to the Prime Ministership. A range of evidence has been produced, in disciplines including political science and media studies, suggesting the existence of systemic gender bias in the mainstream media in English-speaking democracies. This article is the first to compare the media portrayals of Gillard and Turnbull's respective ascensions to leadership, which it does drawing on Judith Butler's concept of gender performativity and using a content and discourse analysis. It contributes further evidence of gender bias in the coverage of political leaders.